Implementation of a shallow geothermal energy system in a multi-source green building - Robert, Gavriliuc; Tiberiu, Catalina; Andrei Stelian, Bejan (CLIMA 2022 conference, 2022)
The building stock is responsible for a large share of greenhouse gas emissions (GHG) in the European Union. Major emission reductions can be achieved through changes in this sector and the building sector is crucial to achieving the EU’s reduction targets. From 2021 all buildings must respect the nZEB standard and must use a certain amount of renewable energy sources. While condensing gas boilers have lower costs these cannot provide cooling and do not use renewable energy. The best alternative is the use of geothermal heat pumps that have high efficiencies and can avoid large amounts of GHG. Currently, geothermal energy sources provide more than 15 GWth for heating and cooling in the European Union, equivalent to more than 4 Mtoe per year, whereby geothermal heat pump systems contribute to the largest part. Shallow geothermal systems are more complex to realize than conventional solutions. Critical aspects include correct design, adequate performance in operation and costs for the installation. The combination with other Renewable Energy Sources (RES) like solar energy could improve the return on investment. The main goal of this paper will be to tackle all the above-mentioned areas by developing and demonstrating the potential of shallow geothermal system to be connected in a precise and efficient way to other renewable sources systems, in particular solar thermal energy. This approach is realized by adapting hybrid solutions to reach nZEB standards through a holistic engineering, construction and controls approach. The demo-site was carried out on an energy-efficient house EFdeN House, an active single-family dwelling that was planned and built in Bucharest for academic and research purposes and it is the first Excellence Research Centre in Romania.